Comparative Study Of Conventional And Precast Methods From The Cost Side (Case Study On Batang III Industrial Worker Flats Construction Project) - Syafriandy Syafriandy (Jurnal Indonesia Sosial Teknologi, 2023)
The Batang III Industrial Workers Flats Construction Project is part of the construction of the Batang integrated industrial estate, where these flats will be a residence for workers in the Batang industrial area later. In the initial design of this project used the full precast upper structure method. This method requires a fairly high implementation cost, so changes were made to the precast / precast VE implementation method. The purpose of the study was to determine the cost efficiency between the upper structure method of full precast, VE precast column multi floor, conventional and choose the type of method that is more economical as an alternative option. This type of qualitative research uses the Value engineering (VE) method, the VE method is one of the well-known methods and has a considerable potential for success in controlling costs. This technique uses an approach by analyzing its function. The process carried out is to reduce cost reduction as far as possible while still paying attention to the desired quality and reliability. The results of this study showed that in the upper structural work of the Batang III industrial worker apartment project, it was found that the initial cost of the full precast method at a cost of Rp. 6,418,779,618,-, the conventional method amounted to Rp. 7,414,918,929, - and the VE precast method multi-floor column joint CCP, precast beam, combination of precast plate and conventional plate in the wet area amounted to Rp. 5,650,987,713, - with a cost difference of Rp. 767,791,904, - or 11.96%, it can be said that the VE precast method multi-floor joint CCP column, precast beam, combination of precast plate and conventional plate in wet areas is cheaper than the full precast method and full conventional method by considering quality results and implementation time